Cultura tributaria de los estudiantes del quinto grado de educación secundaria de la Institución Educativa Rosa Agustina Donayre de Morey, año 2021 - Tafur Navas, Marcia Fernanda (2023)
The present research work entitled "TAX CULTURE OF THE STUDENTS OF THE FIFTH GRADE OF SECONDARY EDUCATION OF THE ROSA AGUSTINA DONAYRE DE MOREY EDUCATIONAL INSTITUTION, YEAR 2021" was carried out with the objective of determining the level of tax culture of fifth grade students of secondary education of the Rosa Agustina Donayre de Morey Educational Institution, year 2021, for this the descriptive type of research was used and the research design was Non-Experimental, 58 students of the fifth grade of education were taken into account as the study population secondary to whom a survey was applied with the data collection instrument called questionnaire; The work concluded that the level of tax culture of the students of the fifth grade of secondary education of the Rosa Agustina Donayre de Morey Educational Institution, year 2021, is high.